Measurement of electronegativity at different laser wavelengths: accuracy of Langmuir probe assisted laser photo-detachment. (13th July 2016) - Sirse, N; Oudini, N; Bendib, A; Ellingboe, A R
Abstract: Langmuir probe (LP) assisted pulsed laser photo-detachment (LPD) of negative ions is one of the frequently used diagnostic techniques in electronegative plasmas. The technique is based on measuring the rise in electron saturation current following photo-detachment. During the photo-detachment process it is assumed that the background electron parameters (temperature and density) remain unchanged in the laser channel and the photo-detached electrons thermalize instantaneously with the background electrons (same temperature). Therefore, the measured electronegativity should be independent of laser wavelengths. However, our recent simulation results (2015 Phys. Plasmas 22 073509) demonstrates a failure of these assumptions and suggests that the measured rise in electron saturation current has a dependence on the laser wavelength. This letter presents experimental evidence in support of these simulation results. In this work, photo-detachment is performed at two different laser wavelengths in an oxygen inductively coupled plasma discharge. Electronegativity measured by LP assisted LPD is compared with those obtained by the hairpin probe (HPP) assisted LPD which is based on quasi-neutrality assumption. The experimental results reveal that the electronegativities measured by LP assisted LPD are affected by the laser wavelength, whereas, electronegativities measured by HPP assisted LPD are almost independent. The discrepancy between the measurements is higher at high electronegativities. In conclusion, the experimental results validate the weakness of assumptions to estimate electronegativity from LPD combined with LP and therefore emphasizes the need of a more realistic model to analyze raw data or an alternate solution is to utilize HPP.